Teori Utilitarianisme Jeremy Bentham: Tujuan Hukum Atau Metode Pengujian Produk Hukum? - Endang Pratiwi; Theo Negoro; Hassanain Haykal (The Constitutional Court of the Republic of Indonesia, 2022)
Utility as a legal purpose has become a belief in Indonesia. In his literature, Bentham implies that utility are the dimension of the calculation of pleasure and pain, which is more appropriate to be used as a method of evaluating laws and regulations, rather than for legal purposes. This study tries to dissect the concept of Bentham's utilitarianism theory, and to find its position in the facet of legal thought. The conclusion of this study explains why utility is not a legal purpose. Utility is part of the calculation variables for evaluating legal product evaluation methods, so as to determine whether legal certainty in a legal product is sustainable or not. Furthermore, Bentham's theory of utilitarianism takes the separability thesis and the reductive thesis, as its standpoint of legal positivism, therefore Bentham's utilitarianism theory is not an independent school of thought, but a facet of legal positivism